Factors of halal food preferences among ACIS students at UiTM Puncak Alam / Nur Syahira Suhaimi - Suhaimi, Nur Syahira (Academy of Contemporary Islamic Studies (ACIS), 2018)
Malaysia is a country consisted of mixed population with three major ethnic groups and various religions. However, Islam is the official religion of the country. Hence, the issue of halal and haram is the great importance to food manufacturers and importers, as well as Muslim consumers. In fact, Muslims around the world are facing the same problem. Thus, the main objectives of this study are determines the factors of halal food preferences among ACIS students. This study applies qualitative approach with the use of in depth interview as the main instrument of data collection. This study consist of data collection method and data analysis. In collection method, it involved library research and interview while in data analysis, it used content analysis to complete this study. Five students were selected as respondents of this study. In general, finding of this study shows that the halal logo, religion, price, family and the cleanliness of each food are the most factors of halal food preferences among ACIS students.